APPLICATION OF EXPERT SYSTEM FOR ANDROID-BASED FOOD LAND SUITABILITY AND HOLTICULTURE - Ramdhani, Lis Saumi; Susilawati, Desi; Saputra, Rizal Amegia (LPPM Universitas Nusa Mandiri, 2020)
Plant land suitability is a way of evaluating the characteristics of planted land-based on certain criteria to determine which types of plants are most suitable for planting in that land, land suitability has not been utilized properly by farmers due to limited knowledge about the varieties of plant types that can be planted in their land, selection The types of plants are still based on traditions and elements of the surrounding agricultural environment which are only limited to a few types of plants without taking into account the suitability of the plants planted to their land characteristics. For this reason, an expert system application was created to help farmers determine the suitability of land for food crops and horticulture on an Android basis because on an Android basis it can make it easier for users, especially farmers to determine the suitability of their land without the need to find a plant land expert and can easily accessible to anyone, anywhere. To produce a good expert system, the research method will be used, namely the certainty factor method. The results of testing expert system applications with certainty factor methods are proven to be able to provide accurate land suitability information